2021
DOI: 10.1002/ejp.1753
|View full text |Cite
|
Sign up to set email alerts
|

Role of the endocannabinoid system in a mouse model of Fragile X undergoing neuropathic pain

Abstract: Background Neuropathic pain is a complex condition characterized by sensory, cognitive and affective symptoms that magnify the perception of pain. The underlying pathogenic mechanisms are largely unknown and there is an urgent need for the development of novel medications. The endocannabinoid system modulates pain perception and drugs targeting the cannabinoid receptor type 2 (CB2) devoid of psychoactive side effects could emerge as novel analgesics. An interesting model to evaluate the mechanisms underlying r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…CBD is a compound typically derived from hemp that targets CB1, CB2 receptors and is an allosteric modulator of μ- and δ-opioid receptors. Evidence in FMR1 knockout mice suggests CB2 receptor is necessary for protection against neuropathic pain, raising interest in targeting this receptor for treatment ( 77 ). A controlled trial examined pain in patients with multiple sclerosis, spinal cord, and other neurological conditions found pain control improved with CBD ( 78 ) in addition to two other studies that found pain relief ( 79 , 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…CBD is a compound typically derived from hemp that targets CB1, CB2 receptors and is an allosteric modulator of μ- and δ-opioid receptors. Evidence in FMR1 knockout mice suggests CB2 receptor is necessary for protection against neuropathic pain, raising interest in targeting this receptor for treatment ( 77 ). A controlled trial examined pain in patients with multiple sclerosis, spinal cord, and other neurological conditions found pain control improved with CBD ( 78 ) in addition to two other studies that found pain relief ( 79 , 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that loss of FMRP decreases nociceptive sensitization in adult mice, even though the basal nociceptive thresholds were intact ( Price et al, 2007 ). Recent evidence also indicates impaired pain induction and perception in the FXS mouse model, including reduced neuropathic pain ( Ramirez-Lopez et al, 2021 ), and visceral pain ( Yang et al, 2020 ). Future in vivo studies will be needed to determine whether and how increased excitability of nociceptive neurons in adolescent mice we observed here is linked to abnormal pain induction or perception in FXS mice.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with FXS commonly exhibit somatosensory deficits, such as hypersensitivity to touch ( Cascio, 2010 ), Self-injurious behaviors in Fragile X individuals ( Arron et al, 2011 ; Crawford et al, 2019 ) are also indicative of abnormal pain perception. Impaired pain induction and perception are also observed in the FXS mouse model, including reduced induction of neuropathic pain ( Ramirez-Lopez et al, 2021 ), and insensitivity to visceral pain ( Yang et al, 2020 ). These and other sensory deficits have been largely attributed to alterations in cortical sensory processing with a wide range of excitability deficits identified in somatosensory cortex of FXS models at neuronal, circuit, and network levels ( Contractor et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies explore the use of exogenous cannabinoids, namely, tetrahydrocannabinol (THC) and cannabidiol (CBD), in various disorders [62,[75][76][77][78][79][80][81], including FXS and ASD [36,58,[82][83][84][85]. Cannabis and targeted eCB system modulation ameliorate symptoms associated with FXS and ASD, including cognitive deficits [37,38], anxiety and hyperactivity [36,39,82], sociability [59,74], restlessness [36], nociception [40,86], and audiogenic seizure susceptibility [39]. However, there is limited knowledge on the neurophysiological effects induced by cannabinoids and the specific mechanisms of how cannabinoids ameliorate FXS symptomatology.…”
Section: The Role Of the Endocannabinoid System In Behaviorsmentioning
confidence: 99%